1990
DOI: 10.1055/s-2008-1071470
|View full text |Cite
|
Sign up to set email alerts
|

CT Findings in Neuronal Ceroid Lipofuscinoses

Abstract: Forty patients suffering from neuronal ceroid lipofuscinosis, 33 of the juvenile type (JNCL) and 7 of the infantile type (INCL), underwent a brain CT. All INCL patients showed severe atrophic changes which were most pronounced supratentorially and in the brainstem. The white matter was hypodense and markedly reduced and the cortical gray matter was quite thin in the oldest patients. The CT signs appeared early and can be used in differential diagnosis. In the JNCL group, CT findings were normal under the age o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
1

Year Published

1995
1995
2009
2009

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 10 publications
0
13
1
Order By: Relevance
“…Magnetic resonance imaging (MRI) studies of motor system deterioration have shown early changes within the cerebellum of diseased patients (Autti et al, 1996; Nardocci et al, 1995). Similarly, studies using computer tomography (CT) scanning techniques, have shown atrophy within the cerebellum in the vermis and lateral hemispheres of JNCL patients, detectable around the age of nine years (Raininko et al, 1990). Comparison of clinical data collected from the patients with imaging data showed a close correlation in atrophy of cerebellar hemispheres and decrease in motor function, balance, and coordination (Raininko et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Magnetic resonance imaging (MRI) studies of motor system deterioration have shown early changes within the cerebellum of diseased patients (Autti et al, 1996; Nardocci et al, 1995). Similarly, studies using computer tomography (CT) scanning techniques, have shown atrophy within the cerebellum in the vermis and lateral hemispheres of JNCL patients, detectable around the age of nine years (Raininko et al, 1990). Comparison of clinical data collected from the patients with imaging data showed a close correlation in atrophy of cerebellar hemispheres and decrease in motor function, balance, and coordination (Raininko et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, studies using computer tomography (CT) scanning techniques, have shown atrophy within the cerebellum in the vermis and lateral hemispheres of JNCL patients, detectable around the age of nine years (Raininko et al, 1990). Comparison of clinical data collected from the patients with imaging data showed a close correlation in atrophy of cerebellar hemispheres and decrease in motor function, balance, and coordination (Raininko et al, 1990). These studies combined suggest that human JNCL patients are succumbing to early anatomical deficits within the cerebellum resulting in progressive motor decline similar to those reported here in the mouse model of JNCL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is in accordance with previous reports showing minimal photoreceptor loss (Cotman et al 2002; Seigel et al 2002), normal electroretinograms (Seigel et al 2002) and alterations in pupillary reflexes only in 24‐month‐old animals (Katz et al 2008). Motor deficits are another major clinical feature of JNCL with early onset, which is mainly attributed to cerebellar degeneration (Raininko et al 1990). In accordance with data from other JNCL mouse models (Eliason et al 2007; Kovacs et al 2006), 8‐week‐old homozygous Cln3 Δex7/8 mice exhibit a marked motor impairment that is evident in the rotarod test.…”
Section: Discussionmentioning
confidence: 99%
“…Juvenile neuronal ceroid lipofuscinosis (JNCL; Batten or Spielmeyer–Vogt disease) is part of a family of fatal lysosomal storage disorders. Progressive visual impairment is typically the first clinical sign of this disease (Consortium 1995; Kohlschutter et al 1993), followed by seizures, cognitive decline and motor dysfunction (Bennett & Hofmann 1999; Raininko et al 1990). Premature death normally occurs around the third decade of life.…”
mentioning
confidence: 99%